Review on Ethical Issues in Ethnographic Study: Some Reflections - Ghimire, Nani Babu (Contemporary Research: An Interdisciplinary Academic Journal, 2021)
Consideration of ethical issues in an ethnographic study is a significant matter to draw trustworthy findings and conclusions for the qualitative researchers. They need to be sensitive and honest on following the principles of ethical consideration while they are engaging in ethnographic research either in data collection or writing research papers. In this paper, I have employed literature review and self-reflective methodology to draw attention of the ethnographers to consider the ethical issues in doing ethnography. The findings and discussion have revealed that the ethnographic researchers should review the ethical aspects of their study from the Institutional Review Board; they must work in a natural setting to discover realistic experiences and/or struggles of the participants by respecting their cultural sensitivity and gaining permission and access to them as voluntary participants in the study. Moreover, the ethnographers need to take informed consent from their participants by securing confidentiality, maintaining anonymity, developing reciprocity, and preserving honesty for them in the research. Likewise, it is found that the ethnographic researcher must be conscious not to harm their participants during research work, and they should not fabricate their data, falsify the interpretation and plagiarize the already published materials in their research paper.